Effect of mulberry galacto-oligosaccharide isolated from mulberry on glucose metabolism and gut microbiota in a type 2 diabetic mice. (December 2021) - Li, Erna; Long, Xiaoshan; Liao, Sentai; Pang, Daorui; Li, Qian; Zou, Yuxiao
Graphical abstract: Highlights: Mulberry galacto-oligosaccharide (MGO) could reduce blood sugar fluctuations in type 2 diabetic mice. MGO alleviates the oxidative stress. MGO up-regulates PI3K/Akt pathways in type 2 diabetic mice. MGO displayed a positive effect in the liver glucose metabolism pathways. MGO was able to change the fecal microbiota in type 2 diabetic mice. Abstract: Mulberry possesses many biological characteristics, such as reduce blood sugar and antioxidant properties, but whether mulberry galacto-oligosaccharide (MGO) can impact the characteristics of the gut microbiota is not yet clear. The objective of this work was to investigate the protective effects of MGO in type 2 diabetic (T2D) mice. The analysis of typical diabetic symptoms and serum status showed that oral MGO alleviated hyperglycemia, insulin resistance and oxidative stress in diabetic mice. These changes were caused by up-regulating the expression of key proteins in the PI3K/Akt pathway, involved in the control of liver glycolysis and gluconeogenesis, and liver glucose metabolism having a positive hypoglycemic effect. Additionally, the gut microbiota indicated that MGO treatment could positively modulate the microbiome composition to decrease the blood glucose in diabetic mice by promoting the growth of Prevotellaceae and Lactobacillus, whereas decreasing the abundance of Lachnospiraceae .